Effect of Salinity on Growth Parameters, Soil Water Potential and Ion Composition in Cucumis melo cv. Huanghemi in North‐Western China. (1st February 2016) - Tedeschi, A.; Zong, L.; Huang, C. H.; Vitale, L.; Volpe, M. G.; Xue, X.
Abstract: A field trial conducted on the melon cultivar Huanghemi irrigated with saline water was carried out in Minqin County in the 2‐year period, 2007 and 2008. In three irrigation treatments, different saline water concentrations were applied, that is 0.8 g l −1 (Control C), 2 g l −1 (Treatment S1 ) and 5 g l −1 (Treatment S2 ), reproducing the natural groundwater concentration in the county. The electrical conductivity of the saline water was as follows: 1.00, 2.66 and 7.03 dS m −1, respectively. The aims of the study were (i) to monitor water consumption and water potential, (ii) assess, during the whole crop cycle, some growth parameters and their relations for estimating the morpho‐functional plant response irrigated with saline water and (iii) determine the ion concentration in different plant tissues to evaluate which mechanism the plant activates in the presence of high salt concentrations. Under salinity stress, the plants sustained the concentration of Ca, Mg and K, but at a level not sufficient to limit the Na adsorption. Therefore, the melon yield decreased and it was determined by a displacement of the ratio K/Na and by a lower ψ t ¯ (total potential MPa). Consequently with increasing salinity, a significant reduction was observed in: water consumption (ETc, mm), leaf area duration (LAD, m 2  d), on shoot dry weight aboveground ( W, g plant −1 ), on specific leaf area (SLA, cm 2  g −1 ) and on leaf area ratio (LAR, cm 2  g −1 ). In treatment S2, in addition to these changes which mainly affected the plant morphology with effects on the biomass produced, a moderate reduction was also observed in net assimilation rate (NAR, g m −2  d −1 ), water use efficiency (WUE), a significant reduction in the energy conversion efficiency (ECE, %) and, in short, in a reduction in the relative growth rate (RGR, g g −1  d −1 ).